Revision of the job characteristics model - Boonzaier, William (Cape Technikon, 2001)
The Job Characteristics Model is widely accepted as a conceptual tool for addressing problems related to employee demotivation, dissatisfaction and marginal performance. The validity of the Job Characteristics Model (Hackman & Oldham, 1980) was assessed by reviewing relevant studies of the model. The review and evaluation are based on studies testing the variables and the relationships between the variables as contained in the model. The reviewed evidence confirmed that the dimensionality of the job characteristics is best represented by the five-factor solution as proposed by the model. The subjective self-report measures of the five job characteristics as formulated by the theory and measured by the revised Job Diagnostic Survey (JDS) were also supported. No evidence was found for the multiplicative Motivating Potential Score (MPS), and as a result the use of a simple additive index of job complexity is recommended as the predictor of personal and work outcomes. Strong empirical support emerged for the relationships between the job characteristics and the personal outcomes. Much weaker relationships between the job characteristics and the work outcomes, however, materialized. Results failed to support the mediating effect of psychological states on the job characteristics/outcomes relationships as specified by the model. The postulated relationships between job characteristics and psychological states were also not confirmed by empirical evidence. The role of growth-need strength, knowledge and skill, and work environment characteristics, as moderators of the relationships between job characteristics and psychological states, as well as of the relationships between psychological states and personal and work outcomes, was seriously questioned.
Thesis (DTech (Human Resources Management))--Cape Technikon, Cape Town, 2001
Keywords: Personnel management; Human resource management